PENERAPAN PEMBELAJARAN KOOPERATIF TGT MELALUI MEDIA PAPAN JURANG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Dedy Setiawan; Sari Yustiana; Muhamad Afandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low learning outcomes of students in addition and subtraction arithmetic operations material, and the learning model used was not centered on the students. This research aims to increase knowledge of improving students' learning outcomes in addition and subtraction arithmetic operations material using the TGT-type cooperative learning model. The subjects in this research were 24 class II students at SDN Kalisari 1 Sayung Demak. This research is classroom action research carried out in two cycles, namely Cycle I and Cycle II, where each cycle consists of planning, action, observation, and reflection. The instruments of this research are documents and tests. Data collection techniques using documentation and tests. The data analysis technique uses qualitative and quantitative descriptive analysis. Qualitative and quantitative descriptions in this research are used to describe improvements in student learning outcomes. The research results increased the average score of students from 55.71 in the pre-cycle to 66.58 in cycle I and then rose to 87.5 in cycle II. This increase occurred because the TGT model encouraged students to become more enthusiastic and active during the learning process, which contributed to improving their learning outcomes. So it can be concluded that the use of the TGT cooperative learning model with the support of gap board media has succeeded in improving student learning outcomes